The Influence of Teacher Creativity, Social Interaction, and Learning Independence on the Learning Motivation - Hidayat, Achmad; Ni’matullah, Onik Farida; Sari, Yuli Ifana (Abjadia : International Journal of Education, 2026)
This research is motivated by the importance of teacher creativity, a conducive social environment, and learning independence as the main factors in shaping student learning motivation. The purpose of the study was to analyze the influence of teacher creativity, social interaction, and learning independence on the learning motivation of grade XI students in social studies at SMAN 2 Pamekasan. The study used a quantitative approach with an associative method. The sample consisted of 65 students selected using a total sampling technique. Data were obtained through a questionnaire that had been tested for validity and reliability, then analyzed using multiple linear regression with the help of SPSS version 22. The results showed that simultaneously the three variables had a significant effect on learning motivation with a contribution of 81.2%. Partially, learning independence provided the most dominant influence of 57.4%, while teacher creativity contributed 24.8% and social interaction 15.6%. These findings emphasize the importance of learning independence, teacher creativity, and social interaction in improving student learning motivation.